Analysis of the safety and immunogenicity profile of an azoximer bromide polymer-adjuvanted subunit influenza vaccine. [version 1; peer review: 2 approved] - Susanna Kharit; Dmitry Lioznov; Michail Kostinov; Ronald Kompier; Tim Hardman; Walter Beyer; Pieter Neels (F1000Research, 2022)
A systematic review of clinical trials conducted with a low-dose inactivated influenza vaccine adjuvanted by azoximer bromide (AZB, Polyoxidonium), was performed to compare vaccine reactogenicity against non-adjuvant vaccines. We also assessed whether lower amounts of antigen per viral strain in AZB-adjuvanted vaccines affected antibody responses. A robust search strategy identified scientific publications reporting 30 clinical trials, comprising data on 11,736 participants and 86 trial arms, for inclusion in the analysis. Local reaction rates (Rlr) appeared to be lower in AZB-adjuvanted vaccine treatment arms versus comparator vaccine treatment arms. Meta‑regression analysis revealed that AZB did not contribute to vaccine reactogenicity. Post-vaccination geometric mean titres in those exposed to AZB-adjuvanted vaccine and comparator vaccine treatment arms were similar in both children and adults aged 18–60 years, implying an antigen-sparing effect by AZB.